A lei 10.639/03 e a prática docente de história na educação básica - Silva, Paula Anunciação (2020)
This dissertation is the result of questions regarding the application of Law 10,639, which, in 2003, amended and included in the Law of Guidelines and Bases the mandatory teaching of African and Afro-Brazilian History and Culture in educational institutions. It has as its object, the practices of teachers of the discipline of History related to these contents, of four schools of the state network of the State of São Paulo. Anchored in the theoretical-methodological framework of authors that, generically, we describe as anti-racists, we chose as contributions for analysis the categories structural racism, awareness, decolonization, anti-racism. We hypothesize the statement that there is a gap between what the Law proposes and the work done at school, whether in the classroom or outside it, through the discipline of History, the one that par excellence, although not exclusively, deals directly with students, referred contents, objects of the legal provision. Of a qualitative nature, for empirical data collection, this research used semi-structured interviews, a procedure carried out with High School History teachers, from the public network of Basic Education in the State of São Paulo. This research demonstrated that there are significant advances in the history schoolwork after the promulgation of Law 10.639 / 03, both in relation to the editorial production related to the proposed contents, as well as the pedagogical action of teachers of this discipline. It is noteworthy, however, that the teaching work depends a lot on the individual initiatives of those educators, whose biographies are marked by a personal engagement in the anti-racist struggle. On the other hand, even teachers who became aware and seek the path of anti-racist education, still carry out work that falls short of the expectations underlying the Law, whether due to insufficient contributions from the managing authorities, whether due to the resistance of a conservative school culture or the conditions pedagogical to which these teachers are submitted, culminating in a still precarious educational, with respect to ethnic-racial issues.